“Plan de marketing para mejorar el volumen de ventas en la ferretería “Feria Del Perno”, En El Cantón La Maná, Provincia De Cotopaxi, Año 2021”. - Becerra Correa, Pedro Jefferson (2022)
The permanence in the market of any company is subject to good administrative management and adequate knowledge that allows decisions to be made for the benefit of the company, in order to safeguard its income to obtain profit. The objective of the project is to analyze a possible marketing plan to improve the volume of sales in the "Feria del Perno" hardware store. The study is cross-sectional, with the use of the survey, and documentary and bibliographical research. The research showed that 58.3% of customers consider the tools necessary to build and maintain the relationship and increase loyalty, and to be able to survive in the competitive market. Also, 56.4% stated that the information provided by vendors is almost always accurate. The owner generally does not use social or digital marketing networks and that is why the need for social networks such as: Twitter, Facebook, and Instagram, to publicize the product or service. The situational diagnosis of the "Feria del Perno" hardware store reflected that the company lacked a marketing plan; there is no organization chart or defined functions of the personnel that work in the institution. For this reason, a more solid marketing plan and structure is proposed that allows the Hardware store a sustainable development over time. The achievement of the economic objectives reaches in a more effective and efficient way by having a previous planning that exposes each one of the steps and the necessary resources to execute strategies that ensure the success of the established goals, through this process the directive can prevent the various threats that are not under the control of the organization's management.